Strategic selection of polliniser trees can improve fruit quality of lychee, a crop that exhibits mixed-mating - Trueman, Stephen J.; Nichols, Joel; Burwell, Christopher J.; Kämper, Wiebke (Basic and applied ecology, 2025)
Fruit trees are often planted in single-cultivar blocks that allow convenient orchard management. This planting design can reduce the opportunities for cross-pollination, decreasing fruit quality if many harvested fruit result from selfing rather than outcrossing. We aimed to: (1) identify flower visitors in a lychee orchard; (2) determine levels of selfing and outcrossing among two lychee cultivars (Kaimana and Kwai Mai Pink) at increasing distances from another cultivar in single-cultivar blocks; and (3) assess effects of pollen parentage on fruit size, skin colour, Brix, acidity, and mineral nutrient concentrations. The European honeybee and a rhiniid fly, Stomorhina discolor, were the most abundant flower visitors. Pollinators appeared to transport cross-pollen at similar levels among the different rows within the single-cultivar blocks. Kaimana trees produced a mixture of selfed and outcrossed fruit. Kwai Mai Pink trees produced more selfed fruit, with at least 75 % being self-fertilised and 19 % being cross-fertilised. Cross-pollination of Kaimana by Souey Tung or Fay Zee Siu increased fruit flesh mass by 27 % and 26 % compared with self-pollinated fruit, respectively, and whole-fruit mass by 20 % and 21 %, respectively. Cross-pollination of Kaimana by Souey Tung also provided the fruit with a small seed and a redder skin. Cross-pollination of Kwai Mai Pink by Wai Chee did not affect the fruit mass or colour compared with self-pollinated fruit. Cross-pollination did not significantly affect Brix, acidity, or mineral nutrient concentrations of Kaimana or Kwai Mai Pink fruit. The results demonstrate that these cultivars have a mixed mating system and that flower visitors transport cross-pollen across many orchard rows. The results also indicate that strategic selection and planting of polliniser cultivars, that provide an optimal pollen genotype, could lead to the production of heavier lychee fruit with improved skin colour and seed size.